Gestational hypertension and progression towards preeclampsia in Northern Ethiopia: prospective cohort study - Awol Yemane; Hale Teka; Sumeya Ahmed; Haftom Temesgen; Elizabeth Langen (BMC, 2021)
Abstract Background Preeclampsia (PE) is one of the main causes of medical complication of pregnancy and is the main cause of perinatal mortality and morbidity. It is one of the top causes of maternal mortality in Ethiopia. Also known as transient hypertension, gestational hypertension (GH) is increased blood pressure during pregnancy without proteinuria, which is expected to return to normal by the 12th-week postpartum visit. PE is GH with proteinuria and /or other systemic manifestations. Evidence from high income countries show that GH significantly progresses towards PE. To our knowledge, this is the first study on the progression of GH towards PE in an African setting. The objective of this study is, therefore, to assess the incidence of GH, progression towards PE and factors associated with progression in Ethiopia. Methods This is a prospective cohort study conducted at Ayder Comprehensive Specialized Hospital (ACSH) and Mekelle General Hospital (MGH), the largest referral centers in Northern Ethiopia. Two hundred and forty women with GH were enrolled and followed up until delivery. Clinical and laboratory data at initial presentation and at follow-up were compared among women who progressed towards PE and who remained with the diagnosis of GH. Logistic regression analysis was employed to model the combined effects of the clinical and laboratory data as significant predictors of progression from GH to PE. Result The incidence of GH in this study was 6 % (4.9-8.5). The rate of progression was 17.1 % (13.4-23.8). Previous history of GH, anemia during pregnancy, previous second-trimester spontaneous abortion were significant predictors of progression. Conclusions There is a high rate of progression of GH towards PE. In a resource-limited setting where predictive and diagnostic tools are scarce, clinical profile of women should be taken into consideration for prediction and diagnosis of PE.